IMPROVING PRONUNCIATION ABILITY THROUGH DUBBING SCENES OF A FILM AT THE ELEVENTH GRADE STUDENTS OF MA NURULHIDAYAH BANDUNG BARAT IN ACADEMIC YEAR 2018/2019 - Mohamad Ikhsan Aditia (IKIP Siliwangi, 2020)
This research paper is written to describe objective dubbing scene a film can improve students’ pronunciation ability and to what extent dubbing a scenes film can improve students’ pronunciation ability at the eleventh grade students of MA Nurulhidayah Bandung Barat.The research design that used in this research was a classroom action research. The research was conducted in two cycles from October 18rd 2018 until November 27th 2018 at the eleventh grade students of MA Nurulhidayah Bandung Barat. The research method of this research is qualitative data. The research data were collected by using techniques of questionnaires, observation, interview, and test (test cycle 1 and 2). The data were analyzed through data presentation that described by a diagram, data conclusion/verification in which is statements that come from the data.The research findings showed that dubbing a scene film could improve the students’ pronunciation ability. The improvement of the students’ pronunciation ability included: a) the students made fewer mistakes in producing particular sounds b) They also made fewer mistakes in reading the dialogue using English stress pattern c) They were able to produce falling intonation e) The mean score is improved from 96.26 for first test, to 97.39 for second test. The research findings also prove that dubbing scene a film could improve classroom situation of pronunciation practice. The improvement of the classroom situation included: a) The students were active in the classroom b) They were able to answer teacher’s questions and were active to give suggestion to the teacher c) They did not refuse to read dialogue in front of the class d) They were cheerful and highly motivated in conducting the lesson e) They paid attention to the teacher, the students did not look bored or make noise. Besides the two findings above, there were other findings as follows: They practiced pronunciation and read the dialogue outside the class. The result of the research implies that English teachers need to choose the appropriate media in teaching pronunciation. The appropriate media to teach pronunciation is dubbing a scenes film.